Indicator-based assessment of wilderness quality in mountain landscapes. (February 2019) - Radford, Sarah Louise; Senn, Josef; Kienast, Felix
Abstract: Wilderness is vitally important: ecologically, economically, socially and culturally, yet it continues to decline globally. Despite high human modification and fragmentation in European landscapes, studies assessing wilderness in Europe suggest the presence of substantial areas of wilderness in mountainous areas. Following a European resolution, the importance of remaining wilderness areas has recently been recognised and efforts towards mapping and protecting remaining wildernesses have increased. The central Alps lie within Switzerland and have been identified in multiple studies as a potential wilderness hotspot in Europe. In this study we develop robust, objective indicators to quantify wilderness and apply them to Switzerland. The indicators account for varying perceptions of wilderness and were evaluated by experts. Assessing international expert opinion to define indicator weightings has not been carried out in similar studies in the past, but serves as a transparent, objective and reproducible approach. The indicators identified high quality wilderness areas, mostly at higher elevations, and demonstrate a suitable method for assessing remaining wilderness areas in landscapes subjected to large modifications by human activities. The spatial distribution of wilderness in the case study region Switzerland suggest that it may play an important role in wilderness conservation in Europe. Our study provides essential baseline information for wilderness monitoring, planning and protection, upon which future studies can build. Above this it provides robust, objective and adaptable indicators for wilderness quantification, which can be implemented in other countries and across various spatial scales. The method can be adapted for other countries – through the use of local expert opinions to weight indicators, and regions – with the inclusion of further datasets.